Suppression of neutrophil accumulation in mice by cutaneous application of geranium essential oil - Oshima Haruyuki; Inouye Shigeharu; Ishibashi Hiroko; Sekimoto Yuka; Maruyama Naho; Yamaguchi Hideyo; Abe Shigeru (BMC, 2005)
Abstract Background Previous studies suggested that essential oils suppressed the adherence response of human neutrophils in vitro and that intraperitoneal application of geranium oil suppressed the neutrophil accumulation into peritoneal cavity in vivo. Usually, essential oils are applied through skin in aromatherapy in inflammatory symptoms. The purpose of this study is to assess the effects of cutaneous application of essential oils on the accumulation of neutrophils in inflammatory sites in skin of mice. Methods Inflammation with accumulation of inflammatory cells was induced by injection of curdlan, a (1→3)-β-D-glucan in skin or peritoneal cavity of mice. Essential oils were applied cutaneously to the mice immediately and 3 hr after intradermal injection of curdlan. The skin with inflammatory lesion was cut off 6 hr after injection of curdlan, and the homogenates were used for myeloperoxidase (MPO: a marker enzyme of neutrophil granule) assay. Results The MPO activity of the skin lesion induced by curdlan was suppressed dose-dependently by cutaneous application of geranium oil. Other oils such as lavender, eucalyptus and tea tree oils also suppressed the activity, but their activities seemed weaker than geranium. Juniper oil didn't suppress the activity Conclusion Cutaneous application of essential oils, especially geranium oil, can suppress the inflammatory symptoms with neutrophil accumulation and edema.